The Flame of the West: A Perspective on the Oxford Inklings' Vision for Imaginative Learning in Christian Scholarship. Issue 3 (December 2022) - Williams, Jay Lennon George
This article will address the power of imaginative learning in Christian formation in personal pedagogy as exemplified in the writings of the Oxford Inklings. Foreseeing the dehumanizing effects caused by an overemphasis on utilitarian education, their collective scholarship in literary fiction helped preserve many ideas that were the treasures of Western thought for millennia. As successful as the Oxford Inklings were in influencing their generation through literary fiction and its power to engage the imagination, using literary fiction for Christian formation remains a largely neglected mode of learning in a culture facing even greater idiological challenges—such as those presented by the Simulation Theory Hypothesis.